2021
DOI: 10.1108/jmh-11-2020-0072
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion of management fads: a popularization perspective

Abstract: Purpose This paper aims to investigate the transience of management fads in the academic and the practitioner-oriented communities to shed light on their roles in the diffusion of fads. Design/methodology/approach This study traces the lifecycles of the following fads in practitioner-oriented and academic journals over more than 50 years: balanced scorecard, business process reengineering, design thinking, knowledge management, learning organization, management by objectives (MBO), matrix organization and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
4
0
3
Order By: Relevance
“…This ultimately remains an empirical question that will have to be addressed in future studies. Research has shown that the lifecycles and trajectories of management concepts and ideas vary considerably [21,93]. Therefore, it will be interesting to follow the future evolutionary trajectory of the Industry 5.0 concept.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This ultimately remains an empirical question that will have to be addressed in future studies. Research has shown that the lifecycles and trajectories of management concepts and ideas vary considerably [21,93]. Therefore, it will be interesting to follow the future evolutionary trajectory of the Industry 5.0 concept.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…More broadly, the analysis can potentially cast light on the processes and dynamics that take place in the early phase of establishing scientific literature and discourse around new management concepts. Therefore, the study can also possibly contribute to our understanding of the birth and emergence of management concepts and ideas [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Por lo tanto, también considera necesaria la distinción entre «fashion» y «fad». Esta última entendiéndola como estallidos espontáneos y no acumulativos del comportamiento de multitudes o efectos «bandwagon» o efecto de arrastre que no concluye en aprendizajes; mientras que «fashion» lo describe como un proceso colectivo de innovación, selección y aprendizaje que responde a los cambios de gusto y sensibilidad e influye en tendencias culturales (Guthey et al, 2021) Ambos conceptos a la final revelan un carácter transitorio y efímero que las define Pollach (2021). Por lo tanto, la modas gerenciales son: una creencia colectiva transitoria difundida por sus creadores bajo la premisa de que una particular técnica logrará al progreso racional de la gestión; o el conjunto de intervenciones innovadoras, racionales y funcionales para fomentar un mejor rendimiento organizativo; o patrones de producción y consumo de un discurso temporalmente intensivo que conducen a cambios organizativos; o simplemente un conjunto de retóricas poderosas que dan forma a la comprensión y las prácticas de la gestión (Pollach, 2021).…”
Section: Discussionunclassified
“…Over time, constructs go through various changes, with the relevance of management research being reevaluated over a 140-year span (Wood et al , 2022), and changes within the management literature (Pollach, 2022) being no different when it comes to how constructs are viewed. Indeed, some concepts become more focused, such as performance management, which in the past 20 years, has undergone a change from firms conducting a once or twice a year evaluation to having “forward-looking, feedback-enriched” systems (Justin and Joy, 2022, p. 428).…”
Section: Overview Of Previous Phases Of Personality Researchmentioning
confidence: 99%